Expression of apoptosis related genes bax, bcl-2 and bcl-X in human gastric cancer: early results of an investigation (Italian Journal of Public Health, 2005)
Background. Evidences indicate an involvement of apoptosis related genes in gastric carcinogenesis. Westudied the gene and protein expression patterns of bcl-2, bax and bcl-X in samples of gastricadenocarcinoma. The apoptotic index values, histological type, differentiation grade, cancer stage andlymph node status were statistically analysed for possible correlations with expressional data.Methods. Thirty specimens of gastric cancer and respective normal control gastric mucosa were collectedfrom patients with the diagnosis of gastric adenocarcinoma who underwent a curative gastrectomy. bcl-2,bax and bcl-XL mRNA and protein levels were respectively determined by reverse transcription PCR (RT-PCR)and western blot using monoclonal antibodies for immunodetection.Results and conclusions. We observed a significant suppression of bax with an increase of bcl-XL at proteinand mRNA levels. The presence of lymph node metastases was statistically related to the loss of baxoverexpression. Bcl-XL was mostly up-regulated in intestinal/mixed types of gastric carcinoma. Theexpression patterns described confirm the role for these apoptosis genes in gastric adenocarcinoma.
Keywords: gastric cancer; apoptosis; bax; bcl-2; bcl-X